2018
DOI: 10.3389/fpls.2018.00429
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Reconstruction of an Old Pedigree of Diploid and Triploid Hydrangea macrophylla Genotypes

Abstract: The ornamental crop species Hydrangea macrophylla exhibits diploid and triploid levels of ploidy and develops lacecap (wild type) or mophead inflorescences. In order to characterize a H. macrophylla germplasm collection, we determined the inflorescence type and the 2C DNA content of 120 plants representing 43 cultivars. We identified 78 putative diploid and 39 putative triploid plants by flow cytometry. In our collection 69 out of 98 flowering plants produced lacecap inflorescences, whereas 29 plants developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
1
14
0
1
Order By: Relevance
“…Until now, only the existence of diploid and triploid H. macrophylla cultivars was reported [5,[8][9][10]. The origin of these triploid H. macrophylla cultivars was unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Until now, only the existence of diploid and triploid H. macrophylla cultivars was reported [5,[8][9][10]. The origin of these triploid H. macrophylla cultivars was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Diploid plants of H. macrophylla contain 2n = 2x = 36 chromosomes and show 2C DNA contents from 3.9 to 5.0 pg. In contrast, triploid plants have 2n = 3x = 54 chromosomes, and 2C DNA contents vary between 6.5 and 7.3 pg [6][7][8][9][10][11]. Recently, a cultivar has been found with a 2C DNA content of 8.9 pg, suggesting tetraploidy [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional possibility, considering the fertility of the triploids, is that a triploid parent may have been used in the breeding of additional triploids. Hempel et al (2018) suggested that sexual hybridization between diploids and triploids was present in the pedigree of many well-known diploid and triploid cultivars. In the current study, controlled crosses between triploid and diploid H. macrophylla plants resulted in aneuploid offspring with differing chromosome numbers and poor growth compared to their parent cultivars.…”
Section: Possible Origin Of Triploid Cultivarsmentioning
confidence: 99%
“…Sexual hybridization between triploids and diploids has been used in a few, diverse ornamental species with fertile triploids like tulip (Tulipa) and pear (Pyrus) to generate genetic variability or new ploidy levels for interspecific hybridization (Cao et al, 2002;Marasek-Ciolakowska et al, 2014). It is unknown whether interploidy crosses between diploid and triploid hydrangeas can be used to develop triploid varieties, although a recent reconstruction of an H. macrophylla pedigree identified at least four putative interploidy crosses that produced high-quality diploid and/or triploid progenies (Hempel et al, 2018).…”
Section: Introductionmentioning
confidence: 99%